Development and validation of next-generation sequencing-based clinical test for triazole resistance prediction in Aspergillus fumigatus - J. R. Caldera; Ashley Dayo; Nathan Wiederhold; Shangxin Yang (Journal of Clinical Microbiology, 2025)
ABSTRACT The rising rates of triazole drug resistance in Aspergillus fumigatus have placed greater reliance on antifungal susceptibility testing (AFST) to guide therapeutic management, particularly in medically complicated patients. Current methods, however, utilize conventional phenotypic assays that may pose significant challenges in performance, result interpretation, and time to reporting. Herein, we developed and validated a next-generation sequencing-based clinical test to predict the AFST phenotype of A. fumigatus against voriconazole, posaconazole, isavuconazole, and itraconazole using the cyp51A genotype as a marker for susceptibility. We sequenced 109 isolates comprising reference and clinical samples from the University of California, Los Angeles, Clinical Microbiology Lab, University of Texas Health Science Center at San Antonio Fungus Testing Laboratory, and the Centers for Disease Control and Prevention and Food and Drug Administration Antimicrobial Resistance Isolate Bank. Additionally, we integrated data from 14 previously published studies to produce comprehensive and robust interpretive criteria for the assay. Despite the complex association between cyp51A mutations and drug resistance, our triazole resistance assay produced a remarkable negative percent agreement (specificity) of ≥95%, thus offering presumptive, yet clinically actionable identification of triazole-wild-type isolates. Clinically, this allows for the rapid discrimination between acquired microbiological resistance in A. fumigatus and observed clinical resistance due to patients’ declining health to help guide the most effective therapeutic management.IMPORTANCEThe rising rates of antifungal resistance have been expressed by many as “the silent pandemic,” profoundly reshaping the landscape of fungal disease management. Innovations in clinical mycology, however, have remained limited, particularly in comparison to the significant advances seen in the greater field of microbiology. Here, we sought to capitalize upon the expanding utility of next-generation sequencing to address a gap in clinical mycology diagnostics and antifungal susceptibility testing. We developed a whole-genome sequencing protocol to evaluate Aspergillus fumigatus cyp51A genotype to predict phenotypic susceptibility to triazole drugs. Our triazole resistance assay offers clinically actionable identification of triazole-wild-type isolates of A. fumigatus in a much more expeditious timeline than traditional phenotypic susceptibility testing.